Product’s Development Strategy and Market Expansion in Development of Traditional Food as a Product of Culinary Excursion in Bali - Wrasiati, Luh Putu; Agung Suryawan W, Anak Agung Putu; Wijaya, I Made Anom Sutrisna; Suter, I Ketut (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2016)
The purpose of this study was to determine the traditional market would be developed as a culinary tourism by the local government of Level II regions (districts / cities), formulation of activities and facilities needed by the strategy of product development and market expansion, implement strategies that had been selected and defined as conduct training, coaching, and mentoring to traders and waiters in traditional markets that have been determined. The results showed that the chosen market that would be developed markets were “senggol” market (night market) of Tabanan City, Kreneng-Asoka Denpasar, Gianyar City, Klungkung City, and City Park Singaraja. Food vendors who were in these markets got guidance regarding the development of products such as ordinances presentation, use of additives, sanitation, and coaching appearance. Market expansion strategy carried out by making brochures, websites "baliwisatakuliner.com" and the provision of traditional food outlets at every event such as the Feast of Balinese art, Buleleng Festival, Festival Vilage Sanur, Nusa Penida Festival, and the annual events in the Anniversary Exhibition of the Republic of Indonesia.